The Effectiveness Of Social Media Promotion Strategy As An Effort To Attract Customer (Nasabah) Interest Using The AISAS Model Approach (Case Study At Bprs Gunung Slamet Cilacap) - Mawadah, Nuri Vina; Hilyatin, Dewi Laela (Wealth: Journal of Islamic Banking and Finance, 2022)
BPRS Gunung Slamet Cilacap is one of the BPRS that implements a promotional mix strategy consisting of advertising, sales promotion, publicity and personal selling. However, since the Covid-19 Pandemic, this promotional strategy has not worked because of social distancing so that BPRS utilizes social media as a promotional medium in order to attract customers. The purpose of this study was to determine how effective the promotion using social media was carried out by BPRS. This research is a field research with a qualitative research type and uses a descriptive analysis approach. The data of this study were collected through observation, interviews, and documentation with marketing and customers of BPRS Gunung Slamet, while data analysis was carried out by data reduction, data presentation and drawing conclusions. The data validity technique uses triangulation. The results of this study indicate that the presence of Instagram and Whatsapp as promotional media for the products of the Gunung Slamet Cilacap BPRS can help in introducing Islamic bank products. The promotions that have been carried out have been effective, as can be seen from the increasing number of customers and effective communication between employees and customers as measured using the AISAS Model (Attention, Interest, Shearch, Action, Share). Based on interviews with marketing and customers of BPRS Gunung Slamet Cilacap, it can be concluded that promotions using social media have succeeded in attracting customers' interest. Customers often see BPRS promoting using social media and are interested, seek further information and then use the product until finally sharing their experiences as customers of BPRS Gunung Slamet. Apart from being a promotional media, social media is also used as a medium of communication between employees and active customers of BPRS Gunung Slamet